2017
DOI: 10.1042/bsr20171104
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal neuroinflammatory and therapeutic role of high mobility group box 1 in ischemic stroke

Abstract: Stroke is a major cause of mortality and disability worldwide. Stroke is a frequent and severe neurovascular disorder. The main cause of stroke is atherosclerosis, and the most common risk factor for atherosclerosis is hypertension. Therefore, prevention and treatment of stroke are crucial issues in humans. High mobility group box 1 (HMGB1) is non-histone nuclear protein that is currently one of the crucial proinflammatory alarmins in ischemic stroke (IS). It is instantly released from necrotic cells in the is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 140 publications
(231 reference statements)
0
37
0
1
Order By: Relevance
“… 27 It is secreted by activated astrocytes and microglia, and stimulates the release of interleukin (IL)-1, TNFα, IL-6 and IL-8, as well as inducible nitric oxide synthase (iNOS) expression. 28 31 An increased vascular and blood–brain barrier permeability is observed. 31 Moreover, matrix metalloproteinase 9 (MMP-9) is upregulated by HMGB1 via TLR4 and its induced cytokines as TNFα or IL-1β mediating cellular death after ischemic stroke.…”
Section: High Mobility Group Boxmentioning
confidence: 99%
See 1 more Smart Citation
“… 27 It is secreted by activated astrocytes and microglia, and stimulates the release of interleukin (IL)-1, TNFα, IL-6 and IL-8, as well as inducible nitric oxide synthase (iNOS) expression. 28 31 An increased vascular and blood–brain barrier permeability is observed. 31 Moreover, matrix metalloproteinase 9 (MMP-9) is upregulated by HMGB1 via TLR4 and its induced cytokines as TNFα or IL-1β mediating cellular death after ischemic stroke.…”
Section: High Mobility Group Boxmentioning
confidence: 99%
“… 28 31 An increased vascular and blood–brain barrier permeability is observed. 31 Moreover, matrix metalloproteinase 9 (MMP-9) is upregulated by HMGB1 via TLR4 and its induced cytokines as TNFα or IL-1β mediating cellular death after ischemic stroke. 31 A maturation process of the passively released protein in the blood circulation to a cytokine-stimulating isoform has been described.…”
Section: High Mobility Group Boxmentioning
confidence: 99%
“…HMGB1signals via TLR2 and TLR4 signaling activate the NF-κB pathway and induce a proinflammatory response [110]. Several studies have shown that plasma levels of HMGB1 increase in ischemic stroke and correlate with poor outcome [111][112][113].…”
Section: Tlr9mentioning
confidence: 99%
“…High mobility group box 1 (HMGB1) is a non-histone, DNA-binding protein that primarily dwells in the nucleus and is associated with the alteration of transcription, DNA repair and chromatin steadiness (108,109,132). Studies have shown that the translocation of HMGB1 out of the nucleus is initiated by it acetylation resulting in its relocation.…”
Section: Resveratrol and Hmgb1 In Gliomamentioning
confidence: 99%